2021
DOI: 10.1007/s00170-021-07296-9
|View full text |Cite
|
Sign up to set email alerts
|

A numerical strategy to identify the FSW process optimal parameters of a butt-welded joint of quasi-pure copper plates: modeling and experimental validation

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…By tracking the material flow into and out of the computational/void domain using a 3D thermomechanical-based CEL approach, Bhattacharjee et al [64] projected surface, subsurface, and volumetric defects. Iordache et al [69] suggested a method based on the CEL approach for identifying the best parameters for a butt-welded joint of copper plates. They drastically cut the simulation duration by employing the mass scaling technique.…”
Section: Initial Statementioning
confidence: 99%
See 1 more Smart Citation
“…By tracking the material flow into and out of the computational/void domain using a 3D thermomechanical-based CEL approach, Bhattacharjee et al [64] projected surface, subsurface, and volumetric defects. Iordache et al [69] suggested a method based on the CEL approach for identifying the best parameters for a butt-welded joint of copper plates. They drastically cut the simulation duration by employing the mass scaling technique.…”
Section: Initial Statementioning
confidence: 99%
“…sub-surface, and volumetric defects. Iordache et al [69] suggested a method based on the CEL approach for identifying the best parameters for a butt-welded joint of copper plates. They drastically cut the simulation duration by employing the mass scaling technique.…”
Section: Initial Statementioning
confidence: 99%